Multiple pathological fractures with a hidden aetiology - S. W. Gnanathayalan; S. Sivageethan; U. Bulugahapitiya (Sri Lanka College of Internal Medicine, 2024)
Bone disease is a well-recognised complication of primary hyperparathyroidism (PHPT). With early diagnosis of PHPT, florid bony changes such as brown tumours, lytic lesions and pathological fractures are rarely seen now. Here, we report an unusual presentation of PHPT in the current era. A 47-year-old lady was evaluated for multiple fragility fractures. Biochemical assessment confirmed primary hyperparathyroidism. DEXA scan showed severe osteoporosis. Left parathyroid adenoma was localised with imaging. She had multiple brown tumours. She underwent parathyroid adenoma excision and recovered after surgery with improved quality of life. Proper evaluation for secondary causes of osteoporosis is vital especially in premenopausal women. Early diagnosis and treatment of PHPT prevent disastrous complications.